Who Really Owns the South China Sea? The Legal Battle Over Artificial Islands (Journal of Asian Development Studies, 2024)
The South China Sea, being one of the most important maritime regions with resources and trading routes, has become one of the world's most disputed regions in the contemporary world. Central to the conflict are artificial islands constructed by states, particularly China, to declare sovereignty and expand maritime zones. However, do these artificial islands have any legal basis that can be recognized under international law? Can UNCLOS shed light on this issue, or does it fail to address artificial manipulations of nature adequately? This paper thus seeks to analyze the legal nature of artificial islands to determine the validity of territorial claims, international courts' reactions, and impacts on regional stability. Is this a prima facie case of a legal vacuum where some states can indulge in acts of aggression, or are we seeing a new law emerging in international maritime law? The results of this article highlight the complex intersection of technology, international law, and geopolitics, particularly in the South China Sea. It shows how, while legally unrecognized under UNCLOS, artificial islands still play a significant role in sovereignty claims and regional stability. The article also stresses the urgent need for legal reforms to adapt to technological advancements. It suggests practical solutions like multinational monitoring and environmental compensation mechanisms to address the growing tension in the region.